Industrial Automation Self-Learning Through the Develoment of Didactic Industrial Processes - Cordeiro, A.; Abraços, M.; Monteiro, L.; Andrade, E.; Foito, Daniel José Medronho (My University, 2017)
Teaching industrial automation is a complex mission. The classical approach is based on lectures and laboratories assisted by teachers. Nevertheless, teaching industrial automation using the classical approach is not easy because this multidisciplinary area requires knowledge in control, energy, electronics, robotics and computer engineering, among others. In this way, this paper presents an approach to teach Industrial Automation based on a self learning strategy. Instead of using the classical approach, students must develop a research work and a didactic automation prototype. The results of this methodology indicate that students increase the interest about industrial automation and clarify important aspects of assembly, commissioning, parameterization and programming of electric and electronic devices. Additionally this methodology seems to increase self-confidence of students and give them the necessary background to face the challenge of working in the real world.
Trabalho apresentado no 20th International Conference on Interactive Collaborative Learning, 27-29 de setembro 2017, Budapeste, Hungria
Keywords: Industrial Automation; Didactic equipment; Self-learning